An Insight into Current IoT Security Methods - Yuen, K.K.; Shim, W.H.; Ting, T.T.; Teoh, C.K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper examines the security methods in the Internet-of-Things. The security methods are carefully studied and categorized into six layers according to the Internet-ofThings framework namely Event Producer and Consumer, Event Queuing System, Transformation and Analysis, Storage, Presentation and Action, and Users and Systems. It can be observed that most security methods emphasizes on Event Producer and Consumer layer whereas the least focused layer is Users and Systems layer. This study aims to present a comprehensive overview to researchers working in the domain of the Internet-of-Things security.